Effect of Biofumigation on Meloidogyne incognita and Microbial Biomass Carbon in Tomato Cultivation - Devindrappa, M.; Umamaheswari, R.; Santhosh, G.; Kumar, C. (University of Jaffna, 2025)
Biofumigation using cruciferous crop residues provides an eco-friendly and sustainable method for managing Meloidogyne incognita and improving soil health in tomato cultivation. This study evaluated the comparative efficacy of mustard, cabbage, cauliflower, and radish residues applied at 0.5%, 1%, and 2% w/w, along with Pochonia chlamydosporia-enriched farmyard manure (FYM) and a chemical nematicide (Velum Prime, Fluopyram 34.48% SC). The incorporation of residues significantly (p≤0.05) reduced nematode infection and reproduction parameters. Among the treatments, mustard at 2% w/w recorded the highest reduction in gall formation (93%) and egg masses (89%) per plant. Principal Component Analysis (PCA) distinctly grouped the high-dose biofumigant treatments (2% w/w) as most effective, with lower infection levels, while 1% applications also showed statistically similar effects in many parameters. Plant growth parameters such as height, shoot and root length, and biomass were significantly enhanced by biofumigation, particularly with mustard at 1% and P. chlamydosporia-enriched FYM. Soil microbial health was also influenced by the treatments. The highest microbial biomass carbon (MBC) was recorded in P. chlamydosporia treatment (310 µg/g), followed by 1% biofumigation treatments (255–285 µg/g), indicating microbial stimulation. However, 2% w/w application slightly reduced MBC (215–230 µg/g), while Velum Prime recorded the lowest (180 µg/g), suggesting suppression of microbial activity. Dehydrogenase enzyme activity followed a similar trend, with the highest activity in P. chlamydosporia (70 µg/g) and the lowest in Velum Prime (41 µg/g). Overall, 1% biofumigation and P. chlamydosporia FYM were most effective in suppressing M. incognita and improving plant and soil health, highlighting their potential for integrated PPN management.
Keywords: Biofumigation; Dehydrogenase enzyme; Microbial biomass; Pochonia chlamydosporia; Root-knot nematode